Enhancing The Indonesian Translation of Quran: Morphological and Historical Semantic Analysis - Anggi Azzuhri (Universitas Darussalam Gontor, 2022)
Translating Qur'an must be conducted with a distinct methodology because of its outstanding features, which other languages cannot accommodate. Despite the terminology, translation of the Qur'an is more similar to Quran exegesis than the definition of modern translation. The difference occurs in the delivery language to which the original text is translated. The gap between Arabic and another language occasionally creates a failure to reach the accurate translation, particularly in the Indonesian Qur’an translation. Encountering the problems: semantic distortion, the linguistic features gap, simplicity of translation, the translation needs to be revised by employing Morphological and Historical Semantic analysis, which several scholars and translators had conducted. These two analyses provide translators with significant help to grasp precisely and translate accurately. In this study, two terms are analysed: tafakkara and hakim. The former term is problematic due to its morphology issue in understanding and translating, which the analysis reveals that the proper translation is kontemplasi than berfikir. The latter term is subjected due to its multiplex meaning. The analysis results in that the translation must be explained further in the additional note. Despite the findings, the initial translator team had done a proper translation for the 60s and 70s; since the Indonesian language develops afterward, the translation becomes partly vague; hence this analysis can tackle this issue.